Immune thrombocytopenic purpura following CoronaVac vaccination: a case report - Turra Aimi, Giulia Eduarda; Bosi, Guilherme Rasia; Guerra, Larissa Beatriz; Michelin, Lessandra (Clinical and Biomedical Research, 2023)
Immune thrombocytopenic purpura (ITP), an autoimmune disorder, has been documented as a result of SARS-CoV-2 infection and a vaccination side effect. The COVID-19 pandemic has led to the creation of CoronaVac vaccine and has been widely administered in Brazil. Patient, in the case, is an 82-years-old female who received the vaccine two days before an acute episode of gingivorrhagia and diffuse cutaneous petechiae. Other exams were made to look for other causes of secondary thrombocytopenia and all the results were normal. The patient showed improvement on the platelet levels three day after the beginning of the treatment with high dosage methylprednisolone. Knowing that other kinds of vaccine can generate ITP, the SARS-CoV-2 vaccine could be related to the symptoms.